Reflections on a career in neurosurgery - Heimburger, Robert F. (Medknow Publications & Media Pvt Ltd, 2013)
Robert Heimburger recounts his career in neurosurgery, including some of the early years of modern neurosurgery and some of the contributions he made, particularly in the areas of early repair of myelomeningocele and spinal cord tethering, high-intensity focused ultrasound for the brain, stereotactic surgery, washing hair and scalps instead of shaving for cranial surgery, and neurosurgical consultation in Asian countries. Now aged 96, he continues to have a keen mind and thorough commitment to the profession that offered him a lifetime of inspiration and service.